The Role of Muslim Families Awareness on The Importance of Entrepreneurship Development in Sokoto State - Alkanchi, Hassan Malami; Mohammed Zaidan, Ashraf; Md Yusoff, Yusmini (Al-Basirah Journal, 2021)
Interest in promoting awareness on entrepreneurship for economic development has been increasing worldwide, but there is no study that explores the gigantic role Muslim families’ awareness on the importance of entrepreneurship development in Sokoto. Entrepreneurship development has been globally recognized as important vehicle for economic development. Muslim families’ awareness has played a significant role in promoting entrepreneurship for economic growth and national development. The major objective of this study is to explore the role of Muslim family awareness on the importance of entrepreneurship development in Sokoto state. Qualitative methodological approach was employed in data collection and analysis. Purposive sampling technique was considered most suitable for this study; the criteria used for selecting the participants were based on relevance, expertise, professionalism and willingness to participate in the study. Semi-structured Interview and focus group discussion was used for the data collection. The participants interviewed included family experts, Muslim family counsellors and Islamic scholars comprising of five (5) participants for each research subject. A total of twelve (15) participants were sampled for the study. This study revealed evidence that; success in advocating entrepreneurship development awareness is through the role of parents in entrepreneurship development, role of Islamic scholars; and role of family and media in promoting entrepreneurship which has a significant impact on Muslim individuals in advancing their business for economic development. However, future research is needed, using quantitative method to explore the gigantic role of Muslim families’ awareness in promoting entrepreneurship for human development in Sokoto state, Nigeria.